2021
DOI: 10.3390/jcm10214812
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Exercise Effects on Human Memory: What We Know and Where to Go from Here

Abstract: Although the acquisition, storage, and retrieval of memories was once thought to happen within a single memory system with multiple processes operating on it, it is now believed that memory is comprised of both distinct and interacting brain systems [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 119 publications
(169 reference statements)
2
24
0
Order By: Relevance
“…It is important to note that acute exercise paradigms are ideally suited to understand the temporal interactions between exercise and phases of memory. In particular, looking at the effects of exercise before the encoding phase and the incorporation of retrieval shortly after suggests these effects may be more specific to encoding mechanisms (Loprinzi et al, 2021). However, to truly disentangle these effects from storage/consolidation, a study that specifically compares pre-encoding versus post-encoding interventions (between the encoding and test phase) would be needed.…”
Section: Post-exercise Improvementsmentioning
confidence: 99%
“…It is important to note that acute exercise paradigms are ideally suited to understand the temporal interactions between exercise and phases of memory. In particular, looking at the effects of exercise before the encoding phase and the incorporation of retrieval shortly after suggests these effects may be more specific to encoding mechanisms (Loprinzi et al, 2021). However, to truly disentangle these effects from storage/consolidation, a study that specifically compares pre-encoding versus post-encoding interventions (between the encoding and test phase) would be needed.…”
Section: Post-exercise Improvementsmentioning
confidence: 99%
“…However, one has to consider that there are few studies that have used exercise durations outside of these ranges, especially on the lower end, and that little is known regarding the moderating mechanisms related to exercise duration. Finally, it seems that benefits from acute exercise were more frequent when exercise type was cycling compared to other forms of exercise (mainly running) [121] , [122] . Although some studies, performed with children and adolescents, have argued that cognitive engaging exercises could have a greater impact on cognition [15] , [123] , [124] , adult studies have found contradictory results [125] [127] .…”
Section: Acute Effects Of Exercise On Cognitive Functionmentioning
confidence: 99%
“…In the human literature, the most prominent effects of both acute and chronic exercise have been demonstrated in mood and executive functions dependent on the prefrontal cortex, such as attention, working memory, cognitive flexibility, and inhibitory control (Chang et al, 2012 ; Basso and Suzuki, 2017 ; Loprinzi et al, 2021 ). Recent findings have also shown evidence of exercise-induced improvements in hippocampal-dependent function including high-interference memory (Déry et al, 2013 ; Heisz et al, 2017 ; Suwabe et al, 2017a ; Bernstein and McNally, 2019 ) and recognition memory (Whiteman et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%